PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aisyah Nuraini Kushidayati; Dhani Ichsanuddin Nur (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
Financial distress is a state in which a company is having financial problems prior to filing for bankruptcy. The company's financial difficulties can be caused by a variety of problems, both internal and external to the company. The study aims to analyze the prediction of financial distress in transportation companies listed on the Indonesia Stock Exchange (IDX) using financial ratios. The financial ratios used are liquidity ratio (QR), profitability ratio (NPM), leverage ratio (Long Term Debt to Total Asset), and activity ratio (Total Asset Turnover). This research was conducted during the 2016-2019 period with a total population of 43 transportation companies, and 25 company data samples were chosen using a non-probability sampling method known as purposive sampling. Logistic regression analysis was used to analyze the data. The results show that the liquidity ratio (QR) cannot contribute to the financial distress, profitability ratio (NPM) can contribute to the financial distress, leverage ratio (LTDTA) cannot contribute to the financial, and the activity ratio (TATO) can contribute to the financial distress of transportation companies listed on the Indonesia Stock Exchange.